Model Customer Engagement Berbasis AI-Driven Personalization pada Platform Digital - Reni Indriani; Melda Yunita; Adi Sismanto (Institut Nalanda, 2026)
This study aims to analyze the effect of AI-driven personalization on customer engagement with multi-platform digital interaction as a moderating variable among students of the Faculty of Islamic Economics and Business (FEBI) at the University of Muhammadiyah Bengkulu. The development of artificial intelligence (AI) technology has encouraged companies to develop more personalized and interactive digital marketing strategies through product recommendations, digital communication, and user-preference-based content presentation. This study uses a quantitative approach with a survey method. The study population was 400 FEBI UM Bengkulu students with a purposive sampling technique, resulting in 200 respondents who met the research criteria. Data collection was carried out through the distribution of online questionnaires using a 5-point Likert scale. The data analysis technique used SEM PLS processed with WarpPLS 7.0. The results of the study indicate that AI-driven personalization has a positive and significant effect on customer engagement. In addition, multi-platform digital interaction also has a positive effect on customer engagement and is able to strengthen the relationship between AI-driven personalization and customer engagement. These findings indicate that the integration of AI-based personalization on various digital platforms can increase customer engagement more effectively. This research provides practical implications for companies developing integrated AI-based digital marketing strategies to enhance customer experience and loyalty.